Meningkatan Kemampuan Membaca Bagi Anak Tunarungu Dengan Menggunakan Media Kartu Bergambar di SLB Dorkas Kakas - Femmy D. Siwi (Peneliti.net, 2022)
This study aims to determine the effectiveness of reading skills for deaf children using picture cards at SLB Dorkas Kakas. This research is included in the type of quantitative research with experimental methods, according to the emergence of variables and the design of single subject research (SSR). The data obtained were analyzed through descriptive statistics and displayed in graphical form. The components analyzed include analysis within conditions and analysis between conditions. Based on the results of data analysis, it can be stated that the ability to read comprehension in deaf children can be increased by using picture word cards as media. This proves that the research hypothesis is accepted. The hypothesis is that if you use picture word cards as media, then the ability to read comprehension of deaf students can increase. From the research data obtained, it can be concluded that the use of picture word cards media can improve reading comprehension skills.